Karakteristik Sifat Kimia Tanah pada Pertanaman Kakao dengan Tingkat Produktivitas Berbeda di Kabupaten Malaka - Elesta Banamtuan; Daniel Fito Adiloksa L Tobing (UNIVERSITAS LABUHANBATU, 2026)
Cocoa productivity is influenced by soil fertility, particularly soil chemical properties that play an important role in nutrient availability for plants. This study aimed to analyze the characteristics of several soil chemical properties in cocoa plantations with different productivity levels in Malaka Regency. The research was conducted in high- and low-productivity cocoa blocks through purposive soil sampling. Laboratory analyses were carried out on several soil chemical parameters, including soil pH, organic C, available N, available P, available K, cation exchange capacity (CEC), and electrical conductivity (EC). The results showed that the high-productivity block had higher levels of organic C, nitrate-N (N-NO₃), available K, and CEC compared to the low-productivity block. Available P content in both blocks was classified as low and was suspected to be a limiting factor for cocoa growth. Soil pH values in both blocks were categorized as neutral and remained suitable for cocoa cultivation. Meanwhile, EC values in the low-productivity block were higher than those in the high-productivity block, indicating greater accumulation of soluble salts in the soil. This condition was supported by the presence of salinity symptoms observed in the field, such as drying and death of cocoa plants in the low-productivity block. Based on the findings, it can be concluded that cocoa blocks with high productivity had relatively better soil chemical properties than low-productivity blocks. Differences in soil chemical properties, particularly organic matter content, available N, available K, CEC, and salinity level, were suspected to influence cocoa productivity in Malaka Regency. Keywords: cocoa, soil chemical properties, productivity, salinity, soil fertility